Correlations between kinematic variables and results in elite male 100-metre sprinters - Antekolovic, L.; Culina, M.; Bakovic, M. (10th International scientific conference on kinesiology. Book of abstracts, 2024)
The aim of this study was to determine the correlations between kinematic indicators of sprint running with the results of the 100m sprint. This research was conducted on a sample of eight (8) athletes and by analysing their results in the 100m final race at the 2017 World Championships in London. The results of the research showed that the crucial role in winning the gold medal was played by the maximum speed and the ability to maintain it until the end of the race. Maximum speed is determined by two parameters - step length and step frequency. The mentioned parameters of step length and step frequency were statistically negatively correlated with a high coefficient of correlation of -0.99. The race interval between 50 and 70 metres is the interval in which the athletes achieved their highest velocities, and after which there was a decrease in the speed in the final part of the race.